Study on screening of fermentation agents and optimization of the fermentation process for pharyngitis tablet residue - Liu, Qian; Zhong, Wei; Yang, Xue; Li, Xiaocheng; Song, Zhuang; Meng, Ying; Liu, Hanlu; Guo, Li; Zhang, Ting (Frontiers in Veterinary Science, 2022)
This study aimed to screen an appropriate starter and determine the optimal fermentation process parameters to optimize the fermentation process of nutrient components and bioactive contents in pharyngitis tablet residue. This study included two experiments. In experiment I, single-factor experimental design was used to study the effects of different biological starters (cellulase preparation; Lactobacillus Plantarum and Bacillus subtilis preparation; mixture of cellulase + Lactobacillus Plantarum and Bacillus subtilis) on the nutritional values and bioactive ingredient contents in pharyngitis tablet residue. In experiment II, orthogonal design experiment was adopted to study the effects of initial water content (45%, 50%, 55%), fermentation temperature (35℃, 37℃, 40℃), and fermentation time (24 h, 48 h, 72 h) on the changes in nutrient components, biologically activity contents, and toxin contents of the residue after optimal fermentation agent treatment. Cellulase preparation was found to be the optimal starter. The optimal fermentation conditions were: initial water content, 55%; fermentation temperature, 37℃; and fermentation time, 72 h. Aflatoxin B1 and vomit toxin were in line with Chinese feed hygiene production standards. The fermentation quality of pharyngitis tablet residue can be improved by using the optimal starter and fermentation conditions.